Kontribusi Mahasiswa KKN 36 UINSU dalam Mengeskalasi Kualitas Desa Pantai Labu Baru, Kecamatan Pantai Labu, Kabupaten Deli Serdang Berbasis Agama, Pendidikan, Ekonomi, dan Informasi dan Teknologi - Annisa Thaharah; Dira Azzahra Putri; Illiyyin Hanifah Maruhawa; Fauzi Arif Lubis (MODELING: Jurnal Program Studi PGMI, 2022)
This devotional scientific article entitled "The Contribution of UINSU KKN-36 Students in Escalating the Quality of Pantai Labu Baru Village, Pantai Labu District, Deli Serdang Regency Based on Religion, Education, Economics, and Information and Technology" is a form of service activity carried out by 25 students from the Faculty of Social Sciences and the Faculty of Economics and Business at UINSU. In the service carried out, UINSU's KKN 36 emphasizes that the aspects used in this service must be continuous with 4 of the 8 bases that have been provided by the committee. Namely the basis of Religion, Education, Economics, and Information and Technology. This service was carried out for 31 days in Pantai Labu Baru Village, Pantai Labu District, Deli Serdang Regency. In this scientific journal article, UINSU's KKN-36 uses qualitative research methods in the process of data collection and research methods, namely by conducting field observations and describing activities or programs of group 36 KKN that have been implemented in Pantai Labu Baru Village.